Cryo-electron microscopy structure of an archaeal ribonuclease P holoenzyme - Futang Wan (Nature Portfolio, 2019)
Ribonulease P is a conserved ribozyme present in all kingdoms of life that is involved in the 5′ maturation step of tRNAs. Here the authors determine the structure of an archaeal RNase P holoenzyme that reveals how archaeal RNase P recognizes its tRNA substrate and suggest a conserved catalytic mechanism amongst RNase Ps despite structural variability.